Fatigue as a moderator in symptom networks of insomnia, anxiety, and depression: insights from moderated network analysis - Xing, Hanyue; Ma, Xu; Meng, Fanqiang; Li, Zhanjiang (Frontiers in Psychiatry, 2025)
BackgroundInsomnia is closely associated with anxiety and depression, forming a complex bidirectional relationship. Although previous research has demonstrated that fatigue is a core and bridge symptom within this complex relationship, its potential moderating role in their interaction remains unexplored. This study employs symptom network analysis to explore the Moderating role of fatigue, aiming to identify core symptoms and their interactions.MethodsA total of 544 participants (mean age 37.86 ± 11.41 years, 210 males) diagnosed with chronic insomnia disorder were included. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), insomnia severity with the Insomnia Severity Index (ISI), anxiety with the Hamilton Anxiety Scale (HAMA), depression with the 17-item Hamilton Depression Rating Scale (HAMD-17), and fatigue with the 14-item Fatigue Scale (FS-14). Hierarchical LASSO was applied to estimate symptom networks, with total scores from the FS-14 used to measure fatigue as the moderating variable.ResultsOur analysis revealed significant bidirectional relationships among symptoms of insomnia, depression, and anxiety. Fatigue played a key moderating role, particularly in the relationships linking difficulty staying asleep with cognitive impairment, somatic anxiety with daytime dysfunction, and difficulty staying asleep with circadian rhythm. Centrality analysis identified mental anxiety, the impact of insomnia on quality of life, and sleep-related interference with daytime function as core symptoms in the network.ConclusionWe identified significant bidirectional relationships between the symptoms of insomnia, depression, and anxiety symptoms and interaction terms moderated by fatigue. These findings provide valuable theoretical and practical insights for disrupting the cycle of these interconnected symptoms through targeted interventions addressing fatigue.